Edukacja Aleksandra i Mikołaja Pawłowiczów Romanowych - Strzelczyk, Agata (Biuletyn Historii Wychowania, 2017)
This article concerns two very different ways and methods of bringing up two Russian tsars – Alexander the First and Nicholas the First. Although they were brothers, one was born nearly twenty years before the second, and that influenced their future. Alexander, born in 1777, was the first son of the successor to the throne, and was raised from the beginning as a future ruler. The person who shaped his education most was his grandmother, empress Catherine the Second. She appointed the Swiss philosopher La Harpe as his teacher, and wanted Alexander to become an enlightened monarch. Nicholas, on the other hand, was never meant to rule and was never prepared for it. He was born in 1796 as the ninth child, and third son, and by the will of his parents, Tsar Paul I and Tsarina Maria Fyodorovna he received an education more suitable for a soldier than a tsar, but he eventually ascended to the throne after Alexander died. One may ask how these differences influenced them and how they shaped their personalities as people and as rulers.